Desarrollo de una aplicación web progresiva para la gestión de archivos asociados a los proyectos del Ministerio de Transportes y Obras Públicas de Pastaza - Arauz León, Ronny Richard (2022)
The purpose this research project is to test the Progressive Web Applications (PWA) technology, through the case study for files associated management with the Transport and Public Works Ministry Pastaza projects. To develop the PWA, it was performed bibliographical research, which helped to structure the theoretical framework, the primary bibliographical sources review and the bibliographic records use. Subsequently, it was agile development practices, which allowed to implement the application, this case was applied the techniques and tools, what they are the most adapted to the project, such as: User Stories, Product Backlog, Sprint, Release Plan, Sprint Review and acceptance Performance Tests. The application is developed under the Django Framework in the Backend, while into Frontend was used MDBootstrap & JQuery. Actually, the app is found in pre-production hosted on the Heroku servers accessible, since the URL https://mtop-pastaza.herokuapp.com/. At the end, it was made the project validation, through the Expert Judgment technique, which participated three professionals from PWA development area, with the got data were applied the Cronbach's Alpha coefficient. by getting, as a result a 1.14 alpha, which represents, both, consistency and reliability, as an Excellent level.